Cryptococcal Osteomyelitis in an Adolescent Survivor of T-Cell Acute Lymphoblastic Leukemia. Issue 6 (June 2015) - Oh, Djin-Ye; Madhusoodhan, P. Pallavi; Springer, Deborah J.; Inglima, Kenneth; Chaudhri, Ali A.; Heitman, Joseph; Raetz, Elizabeth A.; Khaitan, Alka; Rigaud, Mona
Abstract : Cryptococcosis is infrequent in children, and isolated cryptococcal osteomyelitis is rarely encountered. Here, we describe a 14-year-old patient in remission from T-cell acute lymphoblastic leukemia with osteomyelitis because of Cryptococcus neoformans var. grubii . The patient was effectively treated with antifungal therapy. Abstract : Supplemental Digital Content is available in the text.